2021
DOI: 10.31234/osf.io/x9t6n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Critical Evaluation of the FBST ev for Bayesian Hypothesis Testing

Abstract: he “Full Bayesian Significance Test e-value”, henceforth FBST ev, has received increasing attention across a range of disciplines including psychology. We show that the FBST ev leads to four problems: (1) the FBST ev cannot quantify evidence in favor of a null hypothesis and therefore also cannot discriminate “evidence of absence” from “absence of evidence”; (2) the FBST ev is susceptible to sampling to a foregone conclusion; (3) the FBST ev violates the principle of predictive irrelevance, such that it is aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The first two problems identified by Ly and Wagenmakers (2021) are connected to the alleged relationship of the evalue to the frequentist p-value. As an example where the e-value and p-value coincide, they provide the example of Diniz et al (2012) who assumed normally distributed data N (μ, 1) and concluded that under a uniform prior the two quantities become exactly equal.…”
Section: Measure-theoretic Background-the Fbstmentioning
confidence: 99%
See 4 more Smart Citations
“…The first two problems identified by Ly and Wagenmakers (2021) are connected to the alleged relationship of the evalue to the frequentist p-value. As an example where the e-value and p-value coincide, they provide the example of Diniz et al (2012) who assumed normally distributed data N (μ, 1) and concluded that under a uniform prior the two quantities become exactly equal.…”
Section: Measure-theoretic Background-the Fbstmentioning
confidence: 99%
“…(Robert, 2007, p. 232), compare Degroot (1973. Widening their criticism from a single model to the general case, Ly and Wagenmakers (2021) argue that the asymptotic results of Diniz et al (2012) pose a more serious problem, while admitting that for "non-uniform priors the relation between FBST ev and p-value is only approximate" (Ly & Wagenmakers, 2021, p. 5). Diniz et al (2012) showed based on the Bernstein-von-Mises-Theorem (van der Vaart, 1998, Section 10) that for large samples sizes n…”
Section: Measure-theoretic Background-the Fbstmentioning
confidence: 99%
See 3 more Smart Citations